NOx reduction at near ambient temperatures and under lean-burn conditions on modified pd surfaces - Roy, Kanak; Gopinath, Chinnakonda S. (ChemCatChem, 2014)
Palladium surfaces that are modified with O atoms in the subsurface broaden the NO reduction temperature regime up to 325 K with O-2-rich NO+H-2+O-2 compositions. Compared to virgin Pd surfaces, up to 150% higher deNO(x) catalytic activity was observed with modified Pd surfaces at the reaction maximum. Molecular beam instrument and ambient-pressure photoelectron spectroscopy were employed to follow the kinetic and surface changes. These results open up a possibility to realize the cold-start reduction of NOx (deNO(x)). DeNO(x) activity reported in the literature with supported Pd catalysts after a simple calcination in air compares well with our present observations. Surface modification is likely to demonstrate a high potential for other catalytic reactions at relatively low temperatures.
Keywords: heterogeneous catalysis; nitrogen; oxygen; Palladium; surface chemistry

Towards a sustainable and near ambient DeNO(x) under lean burn conditions: a revisit to no reduction on virgin and modified pd(111) surfaces - Roy, Kanak; Jain, Ruchi; Gopinath, Chinnakonda S. (ACS Catalysis, 2014)
Catalytic conversion of NO in the presence of H-2 and O-2 has been studied on Pd(111) surfaces, by using a molecular beam instrument with mass spectrometry detection, as a function of temperature and reactants composition. N-2 and H2O are the major products observed, along with NH3 and N2O minor products under all conditions studied. Particular attention has been paid to the influence of O-2 addition toward NO dissociation. Although O-2-rich compositions were found to inhibit the deNO(x) activity of the Pd catalyst, some enhancement in NO reduction to N-2 was also observed up to a certain O-2 content. The reason for this behavior was determined to be the effective consumption of the H-2 in the mixture by the added O-2 and O atoms from NO dissociation. NO was proven to compete favorably against O-2 for the consumption of H-2, especially <= 550 K, to produce N-2 and H2O. Compared with other elementary reaction steps, a slow decay observed with the 2H + 0 -> H2O step under SS beam oscillation conditions demonstrates its contribution to the rate-limiting nature of the overall reaction. Pd(111) surfaces modified with O atoms in the subsurface (Md-Pd(111)) induces steady-state NO reduction at near-ambient temperatures (325 K) and opens up a possibility to achieve room temperature emission control. A 50% increase in the reaction rates was observed at the reaction maximum on Md-Pd(111), as compared with virgin surfaces. Oxygen adsorption is severely limited below 400 K, and effective NO + H-2 reaction occurs on Md-Pd(111) surfaces. Valence band photoemission with a UV light source (He I) under different oxygen pressures with APPES clearly identified the characteristics of the Md-Pd(111) surfaces and PdO. The electron-deficient or cationic nature of Md-Pd(111) surfaces enhances the NO dissociation and inhibits oxygen chemisorption <= 400 K under lean-burn conditions.
Keywords: deNO(x); heterogeneous catalysis; Hydrogen; lean burn; molecular beam; nitric oxide; Palladium; surface modification